Caregivers in Hemodialysis Patient Care: Psychosocial Burden, Impact on Quality of Life, and Implications for Psychosocial Interventions (Narrative Literature Review) - Aisyah Nilakandi Isjaya; Rezky Putri Indarwati Abdullah; Iin Widya Ningsi (Journal of Community Health Provision, 2026)
Chronic kidney disease (CKD) is a global health problem with a rising prevalence that often requires long-term renal replacement therapy, including hemodialysis. Although hemodialysis can sustain patient survival, this therapy is frequently accompanied by various psychological impacts, such as stress, anxiety, depression, and decreased quality of life. The psychological burden experienced by patients not only affects their individual well-being but also has significant consequences for family members as primary caregivers, manifesting as caregiver burden, emotional, social, and financial strain. This study aims to examine the role of family caregivers in the care of hemodialysis patients, particularly in relation to psychosocial burden, its impact on quality of life, and the implications of psychosocial interventions based on a narrative literature review. The research employed a narrative literature review method by searching scientific articles published between 2020 and 2025 across sources such as Google Scholar, PubMed, and relevant national and international journals. Inclusion criteria were articles that addressed the psychological aspects of hemodialysis patients and their impact on families. The collected data were analyzed descriptively to identify the forms, levels, and impacts of psychological burden. The review found that hemodialysis patients generally experience moderate to severe psychological burden, characterized by anxiety, depression, chronic stress, and reduced psychological well-being. These conditions contribute to an increased caregiving burden for families, including emotional exhaustion, impaired quality of life, social limitations, and financial stress. Adequate family support, psychosocial interventions, and caregiver assistance programs were found to play a crucial role in reducing the psychological burden on both patients and caregivers. In conclusion, the psychological burden of hemodialysis patients has multidimensional consequences for families. Therefore, a holistic care approach involving both patients and families is essential to improve the quality of life for both parties.